Farmer’s reflection on most promising cropping patterns from the TAFSSA on-station research trial at BWMRI, Dinajpur: Comparing diversified cropping patterns in Dinajpur, Bangladesh - Washiq, Faisal; Hossain, Akbar; Aonti, Annika Jahan; Md. Mobinur Rahman; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
Smallholder farmers in Bangladesh primarily engage in rice cultivation during the kharif season with additional crops like maize, mustard, and vegetables grown in the rabi season. Now a days concern has been raised over the sustainability of this system due to natural resource degradation (tillage practices, high wages of labor and overuses of ground water), reduction in profitability and declining yield growth rates. This research note summarizes the farmers reflections from the farmer’s focus group discussion on agronomic research platform trial after the first complete cropping cycle. The trial was established at the Bangladesh Wheat and Maize Research Institute (BWMRI) in Dinajpur, Bangladesh in August 2022.